The Diagnostic Utility of the Basal Luteinizing Hormone Level and Single 60-Minute Post GnRH Agonist Stimulation Test for Idiopathic Central Precocious Puberty in Girls - Cao, Ruixue; Liu, Jinrong; Fu, Pinguo; Zhou, Yonghai; Li, Zhe; Liu, Peining (Frontiers in Endocrinology, 2021)
Objective: The present study aimed to assess the diagnostic utility of the Luteinizing hormone (LH) levels and single 60-minute post gonadotropin-releasing hormone (GnRH) agonist stimulation test for idiopathic central precocious puberty (CPP) in girls. Methods: Data from 1,492 girls diagnosed with precocious puberty who underwent GnRH agonist stimulation testing between January 1, 2016, and October 8, 2020, were retrospectively reviewed. LH) levels and LH/follicle-stimulating hormone (FSH) ratios were measured by immuno-chemiluminescence assay before and at several timepoints after GnRH analogue stimulation testing. Mann–Whitney U test, Spearman’s correlation, χ2 test, and receiver operating characteristic (ROC) analyses were performed to determine the diagnostic utility of these hormone levels. Results: The 1,492 subjects were split into two groups: an idiopathic CPP group (n = 518) and a non-CPP group (n = 974). Basal LH levels and LH/FSH ratios were significantly different between the two groups at 30, 60, 90, and 120 minutes after GnRH analogue stimulation testing. Spearman’s correlation analysis showed the strongest correlation between peak LH and LH levels at 60 minutes after GnRH agonist stimulation (r = 0.986, P < 0.001). ROC curve analysis revealed that the 60-minute LH/FSH ratio yielded the highest consistency, with an area under the ROC curve (AUC) of 0.988 (95% confidence interval [CI], 0.982–0.993) and a cut-off point of 0.603 mIU/L (sensitivity 97.3%, specificity 93.0%). The cut-off points of basal LH and LH/FSH were 0.255 mIU/L (sensitivity 69.8%, specificity 86.0%) and 0.07 (sensitivity 73.2%, specificity 89.5%), respectively, with AUCs of 0.843 (95% CI, 0.819–0.867) and 0.855 (95% CI, 0.831–0.880), respectively. Conclusions: A basal LH value greater than 0.535 mIU/L can be used to diagnose CPP without a GnRH agonist stimulation test. A single 60-minute post-stimulus gonadotropin result of LH and LH/FSH can be used instead of a GnRH agonist stimulation test, or samples can be taken only at 0, 30, and 60 minutes after a GnRH agonist stimulation test. This reduces the number of blood draws required compared with the traditional stimulation test, while still achieving a high level of diagnostic accuracy.